Thrombotic complications in patients with COVID-19 : pathophysiological mechanisms, diagnosis, and treatment - Gasecka, Aleksandra (2020)
© 2020 Springer Nature Switzerland AG. Part of Springer Nature. This article is licensed under a Creative Commons Attribution 4.0 International License. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.